Quantum-chemical study of nucleophilic substitution of nitro group in N-alkyl-3-nitro-1,2,4-triazoles molecules in reactions with alicyclic alcohols and polyatomic phenols - Matulis, Vadim E.; Grigoriev, Yuri V.; Sukhanov, Gennady T.; Krupnova, Irina A.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2018)
Nucleophilic substitution of nitro group in N-alkyl-3-nitro-1,2,4-triazoles molecules with alicyclic alcohols (cyclohexanol, menthol) and polyatomic phenols (pyrocatechol, resorcinol) in the gas phase and in aqueous solution was studied by means of quantum-chemical calculations. The results of calculations show that nucleophilic substitution of the nitro group attached to the triazole ring under action of alicyclic alcohols is thermodynamically possible both in the gas phase and in aqueous solution. Among the isomeric N-alkyl-3-nitro-1,2,4-triazoles, the lowest value of ∆rG corresponds to the N(2)-isomer. Calculated values of ∆rG are appreciably higher for polyatomic phenols in comparison with alicyclic alcohols. The reactions of 1-alkyl-3-nitro-1,2,4-triazoles with resorcinol and pyrocatechol in aqueous solution are characterized by small negative or positive values of ∆rG. So, nucleophilic substitution is reversible in this case. At the same time, the process is irreversible for the corresponding anions (when reactions take place in alkaline media).